PERANAN KREDIT KETAHANAN PANGAN DAN ENERGI DALAM PENINGKATAN PRODUKSI DAN KEUNTUNGAN USAHATANI PADI DI KABUPATEN KAMPAR, RIAU PROVINSI - Ilma Satriana Dewi; Dwi Rachmina; Netti Tinaprilla (DINAMIKA PERTANIAN, 2015)
The majority of farmers with small scale enterprises are still facing a capital shortage primarily rice farming. Capital constraints caused farmers must perform farm activities with a limited input. Limited input causing the output and the revenue generated is not optimal. Food security and energy credits are one of the credit which intends to help especially rice farmers. By the low interest rate, this credit is expected to help farmers for improving the use of inputs and increasing the output and revenue. The aims of study are to evaluate the use of credit on production activities and to analyze the increase in rice farming profits before and after the credits. Research methods used in this research were descriptive analysis, multiple regression analysis, and different test (t-test). The results showed that the rice farmers used KKPE for 53% for rice farming which included the purchase of equipment and farm machinery, production inputs and labor wage. An increase in rice farming profits, but not affected by the credit, and from the t-test result that there was no difference profits before and after credit.